Versatile method for the preparation of conjugates of peptides with DNA/PNA/analog by employing chemo-selective click reaction in water - Gogoi, Khirud; Mane, Meenakshi V.; Kunte, Sunita S.; Kumar, Vaijayanti A. (Nucleic Acids Research, 2007)
The specific 1,3 dipolar Hisgen cycloaddition reaction known as `click-reaction' between azide and alkyne groups is employed for the synthesis of peptideoligonucleotide conjugates. The peptide nucleic acids (PNA)/DNA and peptides may be appended either by azide or alkyne groups. The cycloaddition reaction between the azide and alkyne appended substrates allows the synthesis of the desired conjugates in high purity and yields irrespective of the sequence and functional groups on either of the two substrates. The versatile approach could also be employed to generate the conjugates of peptides with thioacetamido nucleic acid (TANA) analog. The click reaction is catalyzed by Cu (I) in either water or in organic medium. In water, similar to 3-fold excess of the peptide-alkyne/azide drives the reaction to completion in 2 h with no side products.

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Exploration of L-proline-catalyzed -aminoxylation of aldehyde to (S)-guaifenesin-related drug molecules - Panchgalle, Sharad P.; Kunte, Sunita S.; Chavan, Subhash P.; Kalkote, Uttam R. (Synthetic Communications, 2011)
[image omitted] An efficient enantioselective synthesis of (S)-guaifenesin with 99% ee using L-proline-catalyzed -aminoxylation of aldehyde as key step is described and explored for asymmetric syntheses of (S)-moprolol and (R)-methocarbamol.
Keywords: -Aminoxylation; guaifenesin; methocarbamol; moprolol; Proline

Regioselective NaBH4 and DIBAL-H reductions of 3,4-dimethoxyhomopiperonylphthalimide: concise and efficient synthesis of nuevamine and isonuevamine - Wakchaure, Prasad B.; Kunte, Sunita S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2011)
Facile synthesis of nuevamine and isonuevamine has been reported via the regioselectivc reduction of hindered and unhindered carbonyl groups of 3,4-dimethoxyhomopiperonylphthalimide, respectively using sodium borohydridc and diisobutylaluminum hydride, Mowed by an acid catalyzed intramolecular dehydrative cyclization pathways. The chemistry involved in obtaining the regioselectivity has been discussed in brief.
Keywords: 6-dimethoxyhomophthalimide; intramolecular dehydrative cyclizations; isonuevamine; N-Homopiperonyl-5; nuevamine; regioselective reductions; synthesis

Asymmetric N-heterocyclic carbene (NHC)-catalyzed annulation of modified enals with enolizable aldehydes - Yetra, Santhivardhana Reddy; Kaicharla, Trinadh; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
N-Heterocyclic carbene (NHC)-catalyzed highly enantioselective lactonization of modified enals with enolizable aldehydes, proceeding via the alpha,beta-unsaturated acylazolium intermediates, is reported. The reaction results in the asymmetric synthesis of synthetically important 4,5-disubstituted dihydropyranones.

New organocatalyst derived from abietic acid and 4-hydroxy-L-proline for direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Tetrahedron-Asymmetry, 2014)
Enantioselective direct aldol reactions were carried out in aqueous media with a new organocatalyst that was derived from 4-hydroxy-L-proline and abietic acid via a simple and convenient synthetic protocol with a high overall yield (75%). The new organocatalyst was used for aldol reactions between substituted aromatic aldehydes and various ketones in the presence of several acid additives in aqueous media. The corresponding aldol products were obtained in high isolated yields (up to 99%) and with high anti-diastereoselectivities (up to 94%) and enantioselectivities (>99.9%). The catalyst loading can be efficiently reduced to only 1 mol %. The aldol reactions were found to be extremely fast which is very unusual in organocatalyzed reactions in water. (C) 2014 Elsevier Ltd. All rights reserved.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of functionalized cyclopentenes via alpha,beta-unsaturated acyl azoliums - Mondal, Santigopal; Yetra, Santhivardhana Reddy; Patra, Atanu; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Highly enantioselective NHC-organocatalyzed synthesis of functionalized cyclopentenes proceeding via alpha,beta-unsaturated acyl azolium intermediates is reported. The organocascade reaction of modified enals with malonic ester derivatives having a gamma-benzoyl group involves the Michael-intramolecular aldol-beta-lactonization-decarboxylation sequence to deliver cyclopentenes in good yields and excellent ee values.

Smallest organocatalyst in highly enantioselective direct aldol reaction in wet solvent-free conditions - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (RSC Advances, 2014)
The catalytic efficacy of the smallest organocatalyst, L-proline hydrazide, prepared from a cheaply available natural amino acid, such as L-proline, was studied for the direct asymmetric aldol reaction of various ketones with aromatic aldehydes at room temperature in the presence of several acid additives. A loading of 10 mol% of catalyst 1 and p-toluenesulphonic acid as an additive was employed in this reaction, and good yields (up to 99%) with high anti/syn diastereoselectivities (up to 95 : 5) and enantioselectivities (up to >99.9%) were achieved in aqueous media.

Comprehensive study on the effect of acid additives in 1(R),2(R)-Bis[(S)-prolinamido]cyclohexane catalyzed direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
The catalytic efficacy of (1R,2R)-bis[(S)-prolinamido]cyclohexane 1, prepared from the readily available natural amino acid L-proline has been studied for the direct asymmetric aldol reaction of cyclohexanone with substituted benzaldehydes at room temperature in presence of various acid additives. A wide variety of acids e.g. aliphatic fatty acid, chiral acid, sulphonic acid, aromatic acid, etc. have been used as additive for the aldol reaction in aqueous media. A loading of 10 mol% of catalyst 1 is employed in this reaction, and good yields (up to 98% yield), diastereoselectivity (up to 96% de) and enantioselectivities (up to 87% ee) can be achieved in aqueous media within very short reaction time (1-4 hours).
Keywords: acid additives; aqueous media; Asymmetric synthesis; direct aldol reaction; organocatalysis